Clinical consequences of untreated early childhood caries in urban population of children with high risk of caries in Poland - Rożniatowski, Piotr; Piróg-Bednarska, Anna; Kobylińska, Angelika; Gozdowski, Dariusz; Olczak-Kowalczyk, Dorota (Journal of Stomatology, 2017)
Background. The anatomy and low mineral content of primary teeth, especially soon after their eruption, predispose to acute progression of caries. Untreated early childhood caries (ECC) can rapidly lead to destruction of the crown and to pulpal involvement. It is, therefore, important to depict its clinical consequences in relation to caries intensity and age. Aim of the study. To assess the correlation of clinical consequences of ECC with its intensity and age in urban population of children with high risk of caries in Poland. Material and methods. In a group of high caries risk children from Warsaw aged below 6 years the following were evaluated: dental health (decayed, filled, missing teeth due to caries (dmft/dmfs), carious pulp exposure) and mucosal health (ulcerations caused by decayed teeth, fistulae, abscesses (pufa). Four age groups were distinguished: 0 was found in 80% (mean dmft=6.14±5.49, dmfs=11.60±12.92), restorative index was 0.23±0.33. Pufa >0 was observed in 26% (mean 0.853±1.839) with the highest value in the youngest age group (mean 1.20±2.222). Correlations between dmft, dmfs and pufa were observed. Statistically significant correlations were found between teeth missing due to caries and the clinical consequences of untreated caries. Conclusions. The younger the child affected by caries, the more severe the consequences of untreated caries. It has been observed that the rate of consequences increases with caries intensity.